Holocene lake stages and thermokarst dynamics in a discontinuous permafrost affected region, north-eastern Tibetan Plateau. - Opitz, Stephan; Ramisch, Arne; Mischke, Steffen; Diekmann, Bernhard (Journal of Asian Earth Sciences, 2013)
Sediments of a thermokarst system on the north-eastern Tibetan Plateau were studied to infer changes in the lacustrine depositional environment related to climatic changes since the early Holocene. The thermokarst pond with a length of 360 m is situated in a 14.5 × 6 km tectonically unaffected intermontane basin, which is underlain by discontinuous permafrost. A lake sediment core and bankside lacustrine onshore deposits were analysed. Additionally, fossil lake sediments were investigated, which document a former lake-level high stand. The sediments are mainly composed of marls with variable amounts of silt carbonate micrite, and organic matter. On the basis of sedimentological (grain size data), geochemical (XRF), mineralogical (XRD) and micropaleontological data (ostracods and chironomide assemblages) a reconstruction of a paleolake environment was achieved. Lacustrine sediments with endogenic carbonate precipitation suggest a lacustrine environment since at least 19.0 cal ka BP. However, because of relocation and reworking processes in the lake, the sediments did not provide distinct information about the ultimate formation of the lake. The high amount of endogenic carbonate suggests prolonged still-water conditions at about 9.3 cal ka BP. Ostracod shells and chironomid head capsules in fossil lake sediments indicate at least one former lake-level high stand, which were developed between the early and middle Holocene. From the late Holocene the area was possibly characterized by a lake-level decline, documented by a hiatus between lacustrine sediments and a reworked loess or loess-like horizon. After the lake-level decline and the following warming period, the area was affected by thermally-induced subsidence and a re-flooding of the basin because of thawing permafrost.